Предмет: Алгебра,
автор: im9family
Упростите выражение (m-1)^2-4(m+1)^2-6(m+1)(m-1) Заранее спасибо
Ответы
Автор ответа:
0
(m-1)^2 - 4(m+1)^2 - 6 (m+1)(m-1) =
=(m^2-2*m*1+1^2) - 4*( m^2+2m+1^2) -6 (m^2-1^2)=
=m^2-2m+1 -4m^2-8m-4-6m^2+6 =
=(m^2-4m^2-6m^2)+ (-2m-8m)+(1-4+6)=
=-9m^2-10m+3
=(m^2-2*m*1+1^2) - 4*( m^2+2m+1^2) -6 (m^2-1^2)=
=m^2-2m+1 -4m^2-8m-4-6m^2+6 =
=(m^2-4m^2-6m^2)+ (-2m-8m)+(1-4+6)=
=-9m^2-10m+3
Автор ответа:
0
СПАСИБО БОЛЬШОЕ ОЧЕНЬ ВЫРУЧИЛ
Автор ответа:
0
Всегда пожалуйста..
Похожие вопросы
Предмет: Русский язык,
автор: Аноним
Предмет: Химия,
автор: Аноним
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: liliyaelizarova